Spin-orbit torques in locally and globally non-centrosymmetric crystals: antiferromagnets and ferromagnets - Železný, J.; Gao, H.; Manchon, Aurelien; Freimuth, F.; Mokrousov, Y.; Zemen, J.; Mašek, J.; Sinova, Jairo; Jungwirth, T. (American Physical Society, 2017)
One of the main obstacles that prevents practical applications of antiferromagnets is the dfficulty of manipulating the magnetic order parameter. Recently, following the theoretical prediction [J. Železný et al., PRL 113, 157201 (2014)], the electrical switching of magnetic moments in an antiferromagnet has been demonstrated [P. Wadley et al., Science 351, 587 (2016)]. The switching is due to the so-called spin-orbit torque, which has been extensively studied in ferromagnets. In this phenomena a non-equilibrium spin-polarization exchange coupled to the ordered local moments is induced by current, hence exerting a torque on the order parameter. Here we give a general systematic analysis of the symmetry of the spin-orbit torque in locally and globally non-centrosymmetric crystals. We study when the symmetry allows or a nonzero torque, when is the torque effective, and its dependence on the applied current direction and orientation of magnetic moments. For comparison, we consider both antiferromagnetic and ferromagnetic orders. In two representative model crystals we perform microscopic calculations of the spin-orbit torque to illustrate its symmetry properties and to highlight conditions under which the spin-orbit torque can be effcient for manipulating antiferromagnetic moments.